Root-Specific Expression of Vitis vinifera VviNPF2.2 Modulates Shoot Anion Concentration in Transgenic Arabidopsis - Wu, Yue; Henderson, Sam W.; Walker, Rob R.; Gilliham, Matthew (Frontiers in Plant Science, 2022)
Grapevines (Vitis vinifera L., Vvi) on their own roots are generally sensitive to salt-forming ions, particularly chloride (Cl–), when grown in saline environments. Grafting V. vinifera scions to Cl–-excluding hybrid rootstocks reduces the impact of salinity. Molecular components underlying Cl–-exclusion in Vitis species remain largely unknown, however various anion channels and transporters represent good candidates for controlling this trait. Here, two nitrate/peptide transporter family (NPF) members VviNPF2.1 and VviNPF2.2, were isolated. These highly homologous proteins localised to the plasma membrane of Arabidopsis (Arabidopsis thaliana) protoplasts. Both were expressed primarily in grapevine roots and leaves and were more abundant in a Cl–-excluding rootstock compared to a Cl–-includer. Quantitative PCR of grapevine roots revealed that VviNPF2.1 and 2.2 expression was down-regulated by high [NO3−] re-supply post starvation, but not affected by 25 mM Cl−. VviNPF2.2 was functionally characterised using an Arabidopsis enhancer trap line as a heterologous host which enabled cell-type specific expression. Constitutive expression of VviNPF2.2 exclusively in the root epidermis and cortex reduced shoot [Cl−] after a 75 mM NaCl treatment. Higher expression levels of VviNPF2.2 correlated with reduced Arabidopsis xylem sap [NO3−] when not salt stressed. We propose that when expressed in root epidermis and cortex, VviNPF2.2 could function in passive Cl− and NO3− efflux from root cells, which reduces the symplasmic Cl− and NO3− available for root-to-shoot translocation. VviNPF2.2, through its role in the root epidermis and cortex, could therefore be beneficial to plants under salt stress by reducing net shoot Cl− accumulation.